A review of deep-sea shrimps (Decapoda: Dendrobranchiata and Caridea) with four new records for Venezuela - Rodríguez-Quintal, Bladimir; Lira, Carlos (Zootaxa, 2025)
Different explorations have been made in deep waters of the oceans, some of them have included the Caribbean Sea and Venezuela from Albatros R / V in 1884 to Fridtjof Nansen R / V in 1988. Material from the Fridtjof Nansen R/V expeditions in Venezuela’s coasts in 1988 were identified. From a total of 25 species, 4 are first reports for Venezuela: Plesionika tenuipes (Smith, 1881), Plesionika longicauda (Rathbun, 1901), Plesionika martia (A. Milne-Edwards, 1883) and Glyphocrangon alispina Chace 1939, and 21 were previously reported: A total of 80 species of deep-sea decapod shrimp had been reported in Venezuelan territorial waters, representing 12 families and 42 genera. The Acanthephyridae family contributed the highest number of species (14) followed by Sergestidae (9).